Modification of Association of Cystatin C With Kidney and Cardiovascular Outcomes by Obesity - Chen, Debbie C; Scherzer, Rebecca; Ix, Joachim H; Kramer, Holly J; Crews, Deidra C; Nadkarni, Girish; Gutierrez, Orlando; Bullen, Alexander L; Ilori, Titilayo; Garimella, Pranav S; Shlipak, Michael G; Estrella, Michelle M (American journal of kidney diseases, 2024)
Cystatin C-based estimated glomerular filtration rate (eGFR ) has stronger associations with adverse clinical outcomes than creatinine-based eGFR (eGFR ). Obesity may be associated with higher cystatin C levels, independent of kidney function, but it is unknown whether obesity modifies associations of eGFR with kidney and cardiovascular outcomes. Cohort study. 27,249 US adults in the Reasons for Geographic and Racial Differences in Stroke Study. eGFR , eGFR , waist circumference, and body mass index (BMI). All-cause mortality, kidney failure, incident atherosclerotic cardiovascular disease (ASCVD), and incident heart failure (HF). Multivariable Cox and Fine-Gray models with multiplicative interaction terms were constructed to investigate whether waist circumference quartiles or BMI categories modified associations of eGFR with risks of 4 clinical outcomes. Participants had a mean age of 65 years; 54% were women, 41% were Black, and 21% had an eGFR <60mL/min/1.73m . The baseline prevalence of abdominal obesity (waist circumference≥88cm for women or≥102cm for men) was 48% and obesity was 38%. In multivariable adjusted analyses, each 15mL/min/1.73m lower eGFR was associated with higher HR and 95% CI of mortality in each waist circumference quartile (first quartile, 1.19 [1.15-1.24]; second quartile, 1.22 [1.18-1.26]; third quartile, 1.20 [1.16-1.24]; fourth quartile, 1.19 [1.15-1.23]) as well as within each BMI category (BMI<24.9: 1.21 [1.17-1.25]; BMI 25.0-29.9: 1.21 [1.18-1.25]; BMI 30.0-34.9: 1.20 [1.16-1.25]; BMI≥35: 1.17, [1.12-1.22]). Neither waist circumference nor BMI modified the association of eGFR with mortality, kidney failure, incident ASCVD, or incident HF (all P >0.05). Included only Black and White persons in the United States. Obesity did not modify the association of eGFR with all-cause mortality, kidney failure, incident ASCVD, or incident HF. Among individuals with obesity, cystatin C may be used to provide eGFR-based risk prognostication for adverse outcomes. Cystatin C is increasingly used in clinical practice to estimate kidney function, and cystatin C-based eGFR (eGFR ) may be used to determine risk for adverse clinical outcomes. Adiposity may increase serum levels of cystatin C, independent of kidney function. This cohort study investigated whether associations of eGFR with adverse kidney and cardiovascular outcomes are modified by measures of obesity, waist circumference, and body mass index. We found that obesity does not modify associations of eGFR with 4 clinical outcomes and conclude that among individuals with obesity, cystatin C may be used to provide eGFR-based risk prognostication for adverse outcomes.